The policy of modernization of legal education at the national and global levels - N. N. Pachina; A. R. Fedotov; L. V. Nabokov; T. A. Shchebzukhova (Современная наука и инновации)
The purpose of this work is to study the modernization policy, which focuses on sociostructural, normative and value changes in the field of education. The modernization of legal education is revealed at various levels of functioning: global, national. Definitions of the concepts «education», «juridical education», «modernization» and «modernization models» are given in this article. Modern approaches to the modernization of legal education both in the Russian Federation and in a number of foreign countries have been studied. The national and global levels are determined in the models of modernization of legal education. In conclusion are proposed the ways of modernizing of juridical education, which will both improve the quality of education and optimize and modernize the possibility of obtaining it.